Starburst accelerator and incubator construction & energy: How to monitor the activities of an incubator and give strategic advice to startups - Kiel, Hannah (2014)
This work project takes the format of a problem-solving approach suggested by “Impulse Partners”, a French consulting firm. It recommends a way to measure the success of ten startups in the incubators “Starburst” and “Incubator Construction & Energy” and give them strategic guidance. A Balanced Scorecard is elaborated to help incubated startups building up and implementing their strategy. The Scorecard suggests possible initiatives for the startups that are ideally realized with the help of the consulting firm that is steering the incubator. Special attention is drawn to what the startups need to succeed, which typically concerns financing, networking and managing skills.